The Historical Background of the English Lectionary of 1955 - Willis, Geoffrey Grimshaw (The journal of ecclesiastical history, 1958)
The preface to the Book of Common Prayer, entitled Concerning the Service of the Church since 1662, but before that simply The Preface, was derived substantially from the preface to the revised Breviary of Quiñones, which was one of the sources for the revised daily offices of the Church of England. It appeals from what it considers the corruptions of the medieval office to the ‘godly and decent order of the ancient Fathers’. This order, it says, was devised for the systematic reading of holy scripture in the offices of the Church, and it was the intention of the compilers of the English Prayer Book to restore such a regular order of reading for the instruction of the people. It represented a revolt against three features of the lessons in the medieval breviary: first, against the frequent interruptions of the reading of scripture in course by the occurrence of feasts with proper lessons; secondly, the lack of completeness and continuity in the lessons themselves; and thirdly, the use of non-biblical material in the lessons. Even if the daily office of the breviary, which is based on the ecclesiastical year, were not interrupted by any immoveable feasts having proper lessons, it would still not provide for the reading of the whole of scripture, as its lessons are too short, and also the variable lessons are confined to the night office.